Analisis Manajemen Pasraman Dalam Mewujudkan Sisya Yang Cerdas Berbudaya Pada Pasraman Padma Bhuana Saraswati Yogyakarta - Supriyoko; I Nyoman Santiawan (Media Manajemen Pendidikan, 2022)
This study aims to determine Pasraman management, inhibiting and supporting factors, how to overcome inhibiting factors and the results of Pasraman education in realizing culturally intelligent students at Padma Bhuana Pasraman Yogyakarta. The approach used in this research is a qualitative approach with a descriptive method. The technique used in data collection is by direct observation, direct interviews and documentation. Data obtained from observations and interviews with informants were analyzed using triangulation data analysis techniques. The results of the study are: 1. Padma Bhuana Saraswati Pasraman Management carries out planning, organizing, implementing and controlling together. Planning is done by determining fixed programs, short-term programs and long-term programs. Organizing by dividing groups of types of activities and assigning teachers and pasraman managers. The groups are divided into 3 groups, namely religious learning groups, arts and culture learning groups and social activities groups. Implementation of the program is carried out regularly every Saturday starting at 09.00-15.00 for religious learning groups and arts and culture groups. Meanwhile, for the group of social activities, preparations are carried out before the activities are carried out with the intensity of time as needed. In the supervision, the manager applies the attendance method and learning evaluation. Education management carried out with the cooperation of teacher managers and parents is very much needed in the success of learning activities at the Padma Bhuana Saraswati Pasraman; 2. Supporting factors and inhibiting factors in providing education are: Supporting factors, namely the solidity of the core management, parental commitment, government support and support from pasraman teachers. Some of the inhibiting factors are the limited time of parents, the presence of new members and the condition of the students who get bored quickly; 3. The inhibiting factor step is to use an area/block system that is used to collaborate with or invite to go together when parents cannot deliver students. The steps taken to overcome the limitations of new members are to carry out intense socialization and provide special attention and services, while to overcome the boredom of students quickly are to convey creative, innovative learning and insert games that provide prizes and punishments; 4. The results of education at Paraman Padma Bhuana Saraswati are shown by six indicators, namely pasraman students who have ethics/morals, independence, social care, achievement, able to preserve culture and commitment to the state as well as high tolerance.